A study of Hepatitis B virus infection using chi-square statistic. Issue 1 (January 2021) - Odetunmibi, Oluwole A; Adejumo, Adebowale O; Anake, Timothy A
Abstract: Hepatitis B is caused by the hepatitis B virus (HBV) and it affects livers. It has been established that the disease is a serious medical condition caused by an overpowering immune response to infection. To this effect, there is a need for cross examination of records of patients on this disease to ascertain the factors that could be responsible for the survival or dying from this disease. Descriptive analysis of the data showed that sexually active age bracket (31 – 50) are greatly affected by the disease while female accounted for majority of those that are tested positive to the disease. Chi squared statistic was used to test for independence between age and gender of those who tested positive to disease between 2006 and 2015 in Lagos state, Nigeria. It was discovered that, both variables of age and gender are not independent which means there is association between the Age and Gender of HBV patients.